Toleransi Remaja Islam Kepada Pemeluk Agama yang Berbeda: Studi Ekstrakurikuler Rohani Islam (Rohis) SMA di Bekasi, Jawa Barat - Ismi Apriliani; Hatim Ghazali (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2016)
Diversity is a blessed but also can be a cause of destructive conflict like already happened at some places in Indonesia. Based on that fact, tolerance is a value that needs to be inculcated to every student, through co curricular and extra-curricular activity like Moslem Youth Community at school. This research aims to describe about tolerance categories Moslem Youth Community member of a school in Bekasi. Method of this research is qualitative and data collected by interview and document analysis. Participants were chosen based on purposive sampling that include its coordinators, teacher who in charge for that extra-curricular, and mentor. This research got result that Moslem Youth Community of that school accept and respect to diversity based on their awareness, and they give others chances to do their worship, although they did not do an action to support it. In conclusion, that Moslem Youth Community is in passive tolerance category.Keywords: Tolerance, Youth, ROHIS, Multicultural Education, Diversity.